Hierarchical LiZnVO4@C nanostructures with enhanced cycling stability for lithium-ion batteries. Issue 17 (7th May 2015) - Zeng, Lingxing; Huang, Xiaoxia; Zheng, Cheng; Qian, Qingrong; Chen, Qinghua; Wei, Mingdeng
<x xml:space="preserve">Abstract</x> Hierarchical LiZnVO4@C nanostructures composed of thin nanobelt aggregates were synthesized for the first time and they exhibited a high performance for LIBs.